Impacts d’outils de gestion sur la conduite de cultures en pépinière - Valérie Pueyo; Valérie Zara-Meylan (Activités)
This paper aims to show the impact of using management tools on nursery crop production. It is based on more general research carried out in a large nursery which had introduced tools for employee performance specification and assessment, in order to “rationalize” the organisation of production. Since the cultivation of plants in pots (living, perishable products) is a series of long, unstable procedures undertaken in a dynamic environment, this analysis covers the impact the tools had on the work of employees involved in cultivation and dispatch, as well as on the sustainability of the company.Furthermore, analysis of the interviews and observations reveals that the conditions for time management are typified by uncertainties and unknown factors, whereas the deadlines constitute imperatives in a business with a significant physical component. The situation is made worse by the new specification and assessment tools, which are rigid, simplistic, and run counter to the demands of the job. They hamper the development of activities within an individual and collective dynamic, and prevent the possible emergence of actions that would coherently integrate efficiency targets. The consequences are apparent in terms of potential threats to health and safety, quality and the sustainability of the production system.